The influence of mid-latitude cyclones on European background surface ozone - K. E. Knowland; R. M. Doherty; K. I. Hodges; L. E. Ott (Atmospheric Chemistry and Physics, 2017)
The relationship between springtime mid-latitude cyclones and background ozone (O 3 ) is explored using a combination of observational and reanalysis data sets. First, the relationship between surface O 3 observations at two rural monitoring sites on the west coast of Europe – Mace Head, Ireland, and Monte Velho, Portugal – and cyclone track frequency in the surrounding regions is examined. Second, detailed case study examination of four individual mid-latitude cyclones and the influence of the associated frontal passage on surface O 3 is performed. Cyclone tracks have a greater influence on the O 3 measurements at the more northern coastal European station, Mace Head, located within the main North Atlantic (NA) storm track. In particular, when cyclones track north of 53° N, there is a significant relationship with high levels of surface O 3 (> 75th percentile). The further away a cyclone is from the NA storm track, the more likely it will be associated with both high and low (< 25th percentile) levels of O 3 at the observation site during the cyclone's life cycle. The results of the four case studies demonstrate (a) the importance of the passage of a cyclone's cold front in relation to surface O 3 measurements, (b) the ability of mid-latitude cyclones to bring down high levels of O 3 from the stratosphere, and (c) that accompanying surface high-pressure systems and their associated transport pathways play an important role in the temporal variability of surface O 3 . The main source of high O 3 to these two sites in springtime is from the stratosphere, either from direct injection into the cyclone or associated with aged airstreams from decaying downstream cyclones that can become entrained and descend toward the surface within new cyclones over the NA region.